(3GdLhgQ GdKejf aj fNH SjQ GdCejfs - (3CMeO Hf Hjdjc GdeMSfj GdXGgQj GdTGaYj GdeUQj, TgGH GdOjf,J (B753 (3g` s ((3GdeDdas)
(3ChdgG (B:s
(3GdMeO ddg hSdGe Ydi YHGOg GdPjf GUWai s
(3BNQgG (B:s
(3JeJ GdSjQI GdfHhjI s
(3HChdgG dhMI ePgHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B106 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B357 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B111s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B54 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B112 s
Keywords: (3GdJGQjNs